Synthetic illicit opioids in Brazil: Nitazenes arrival - Karen Rafaela Gonçalves de Araújo; André Luis Fabris; Luiz Ferreira Neves Junior; Alexandre Learth Soares; Jose Luiz Costa; Mauricio Yonamine (Forensic Science International: Reports)
Purpose: While illicit opioids have not been historically significant in Brazil, these numbers have increased in the last few years. This change in the drug scenario is mainly associated with synthetic opioids, a class of new psychoactive substances (NPS). In this context, the present article describes detailed information about the recent cases of synthetic opioids seized in Brazil, especially the nitazenes group. Methods: All the analyses were carried out by the Superintendence of the Technical-Scientific Police - Narcotics Control Center (STSP-NCC) in São Paulo, between July 2022 and April 2023. The synthetic opioids were mainly found in herbal fragments. Results: Nitazenes, were the most frequent drugs detected in the seizures that took place in the State of São Paulo. There was a total of 140 cases of opioids seizures and 95 % out of those belonging to the nitazene group, while only 5 % consisted of other opioids (morphine and fentanyl). Nitazenes were found 28.6 % isolated and 71.4 % mixed with other active compounds, being MDMB-4en-PINACA the most prevalent (30 % of the samples). Non-nitazenes were found 27.1 % mixed and 72.9 % isolated. Nitazenes and non-nitazene opioids were not found in association in any sample. Conclusion: This is the first consistent report of nitazene opioids apprehensions in Brazil. Also, as far as we know, it is the first report in which nitazenes were detected in the form of herbal fragments. The effect of smoking a potent opioid together with synthetic cannabinoids is unpredictable and most users cannot be aware of what they are using.